Partisipasi Masyarakat Dalam Upaya Memaksimalkan Potensi Ekonomi Dan Pariwisata Kawasan Super Prioritas Nasional (KSPN) Labuan Bajo Di Kabupaten Manggarai Barat - Mary Ismowati; Dwi Pharadilla Rizon; Ahmad Said Saputra; Azizah Azizah; Halimah Nur Rahmawati; Haniefa Bilqis; Muhamad Suhuf Abie Bakri (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2022)
The increase in economic potential in the tourist area of KSPN Labuan Bajo, West Manggarai Regency, in maximizing the potential for economic and tourism wealth, especially related to several SMEs in Labuan Bajo, of course requires community participation. It aims to maximize the potential of economic and tourism wealth, by maximizing various local wisdoms. The research method used is qualitative by conducting interviews with related parties. The results showed that the Central Government, namely the Coordinating Ministry for Creative Economy and Perumda Bidadari, West Manggarai Regency, had provided opportunities for people in the tourist area of KSPN Labuan Bajo to participate. There is a willingness of the community to participate, as well as the ability of the community to participate. There are 3 types of levels of community participation in tourism in the Labuan Bajo area, namely a. implementation level, b. level of utilization of results and c. evaluation level. However, participation at the planning level does not yet exist. This means that the community has not been involved in the tourism planning process in Labuan Bajo.